REKOMENDASI LAPTOP TERHADAP CALON PEMBELI PT. GENIUS COMPUTER CENTRE MENGGUNAKAN SIMPLE ADDITIVE WEIGHTING - Ursipuny, Natasha; Angriani, Husni; Pontoh, Zaenab (JTRISTE, 2024)
This research aims to implement the Simple Additive Weighting (SAW) method in providing recommendations to potential laptop buyers at PT.Genius Computer Centre. Various laptop variants with different brands and specifications make it difficult for potential buyers to choose a laptop that suits their needs. The implementation of the SAW method is used as a basis for recommending laptops based on user requirements. SAW is a commonly used method in decision-making and involves assessments based on predefined criteria weights. The results of the SAW calculations provide recommendations for laptops that meet the user's needs, helping potential buyers choose a laptop that fits their requirements. The implementation of the SAW method in the decision support system can address the difficulties faced by potential laptop buyers at PT. Genius Computer Centre in choosing a suitable laptop and provide recommendations that can enhance their understanding of the required laptop specifications. This research has the potential to significantly improve the laptop shopping experience for potential buyers.